Mucosal-associated invariant T cells in patients with axial spondyloarthritis - van der Meer, Rienk Gerben; Spoorenberg, Anneke; Brouwer, Elisabeth; Doornbos-van der Meer, Berber; Boots, Annemieke M. H.; Arends, Suzanne; Abdulahad, Wayel H. (Frontiers in Immunology, 2023)
Background Several studies implicate Th17-cells and its cytokine (IL-17) in disease pathogenesis of spondyloarthritis (SpA), with available evidence supporting a pathogenic role of CD8+ T-cells. However, data on the involvement of CD8+ mucosal-associated invariant T-cells (MAIT) and their phenotypic characterization and inflammatory function including IL-17 and Granzyme A production in a homogenous population of SpA-patients with primarily axial disease (axSpA) are lacking. Objectives Quantify and characterize the phenotype and function of circulating CD8+MAIT-cells in axSpA-patients with primarily axial disease. Methods Blood samples were obtained from 41 axSpA-patients and 30 age- and sex-matched healthy controls (HC). Numbers and percentages of MAIT-cells (defined as CD3+CD8+CD161highTCRVα7.2+) were determined, and production of IL-17 and Granzyme A (GrzA) by MAIT-cells were examined by flow cytometry upon in vitro stimulation. Serum IgG specific for CMV was measured by ELISA. Results No significant differences in numbers and percentages of circulating MAIT-cells were found between axSpA-patients and HC. Further phenotypic analysis revealed a significant decrease in numbers of central memory MAIT-cells of axSpA-patients compared to HC. The decrease in central memory MAIT-cells in axSpA patients was not attributed to an alteration in CD8 T-cell numbers, but correlated inversely with serum CMV-IgG titers. Production of IL-17 by MAIT-cells was comparable between axSpA-patients and HC, whereas a significant decrease in the production of GrzA by MAIT-cells from axSpA-patients was observed. Conclusions The decrease in cytotoxic capability of circulating MAIT-cells in axSpA-patients might implicate that these cell types migrate to the inflamed tissue and therefore associate with the axial disease pathogenesis.